The role of digital technology in strengthening leadership effectiveness for MSMEs financial performance - Sambodo, Bambang; Suhardjanto, Djoko; Honggowati, Setianingtyas; Probohudono, Agung Nur (International Journal of Innovative Research and Scientific Studies, 2025)
This research examines the influence of leadership competencies on the financial performance of micro, small, and medium enterprises (MSMEs) in Indonesia, emphasizing the moderating role of digital technology. Despite their vital contribution to gross domestic product (GDP) and employment, MSMEs face persistent financial vulnerabilities. To address this, the study categorizes leadership into six competencies: ability to lead, entrepreneurial spirit, knowledge, communication, teamwork, and problem-solving, grounded in trait, behavioral, and contingency theories. The Knowledge-Based View (KBV) further informs the examination of digital technology as a moderator of the effects of knowledge and communication. Survey data were collected from 187 MSME owners in the Riau Islands Province. Using multiple and moderated regression analysis, the results show that all six leadership competencies significantly enhance financial performance. Additionally, digital technology strengthens the positive effects of knowledge and communication. These findings underscore the synergistic interaction between leadership behavior and digital capability in driving MSME resilience and performance. The study contributes to the literature by integrating classical leadership theories with KBV within the digital economy context of an emerging market. Practically, it offers insights for policymakers and development agencies to design integrated leadership and digital training interventions tailored to MSMEs’ needs.